Livelihood Strategies and Adaptation of Sonok Cattle Farmers During the COVID-19 Pandemic - Safariyah, Laelatus; Zuhriyah, Amanatuz; Widodo, Slamet (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
Madura is an area in Indonesia that is well-known for its high cattle population. However, like many other industries, the Sonok cattle business in Madura has been greatly impacted by the COVID-19 pandemic. In order to determine the extent of this impact, as well as the adaptation and livelihood strategies of Sonok cattle farmers, a study was conducted in West Dempo Village, Pasean District, Pamekasan Regency. This village is the center of superior Sonok cattle and the origin of their existence. The study used descriptive statistics as its method and found that the pandemic has caused a decline in the prices of Sonok cattle and lowered the motivation of farmers to buy them. As a result, farmers have had to adapt and reduce costs wherever possible. The access to capital owned by Sonok cattle breeders, however, is relatively good and is used to form a livelihood strategy. These strategies include on-farm strategies, multiple livelihood patterns, and migration. In response to the pandemic, some farmers have also added other farm animals, such as fighting chickens, to their livelihood strategies.